Effect of Electromagnetic Radiations On Human Body - Ohlan, Rahul (International Journal of Computer Sciences and Engineering, 2018)
Mobile phones has become the integral part of human life in today’s world. The data shows that the total number of mobile phone users has been increased to 4.68 billion and is expected to reach 5 billion mark in 2019.Indians are second highest user 1,183,408,611 in numbers after China in may 2018. But every coin has two sides similarly here also one negative side of mobile phones is on human brain. Radiation of electromagnetic waves created a negative impact on human’s brain and their immune system. In recent years numerous ways such as (earphones, bluetooth, headset) has been investigated to reduce this harmful effect of EM wave .These frequencies are reducing human health exponentially. In this paper effect of EM waves with or without devices has been discussed.